Analisis Tata Letak Gudang Produksi di PT Nusantara Sejahtera Medica - Umayatul Azizah; Denny Murdani (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Tight business competition encourages companies to manage resources optimally and create competitive advantages. Operations management, which includes managing inputs, processes, and outputs, plays an important role in achieving these goals. Warehouses are an important part of a company's supply chain, functioning as a place to store goods inventory and support the smooth production and operational processes. Optimal warehouse layout influences smooth operations, optimizes space, and supports the production process. PT Nusantara Sejahtera Medica is a company engaged in the production of organic fertilizer and health supplements in West Bandung Regency, currently using a "play out by process" system in its warehouse. This system is considered less than optimal and needs to be reviewed to improve operational effectiveness. This research aims to analyze the layout of the production warehouse and how efficient it is in the production process at PT Nusantara Sejahtera Medica to increase operational effectiveness. This research use desciptive qualitative approach. Data was obtained from direct observation, interviews and documentation. The research results show that PT Nusantara Sejahtera Medika implements a "play out by process" layout in its warehouse, aiming to minimize material handling costs and maximize storage space. However, there are problems such as delays in work activities caused by damage to machines and boxes, which hamper the production process. Apart from that, at PT Nusantara Sejahtera Medika, there are three main warehousing activities, including movement, storage and information transfer. Although the company had implemented FIFO inventory management methods, the outdated warehouse layout and less innovative communication system indicated the need for a review to improve operational efficiency.